Kemanfaatan Artificial Intelligence Bagi Mahasiswa Di Universitas Muhammadiyah Riau - Azmi, Zul; Pernando, Olipian Resky; Putri, Yolanda Arsita; Putri, Naiya Aulia (Politeknik Negeri Padang, 2024)
Artificial Intelligence (AI) is a sophisticated technological development or a system that includes the use of algorithms and computers to model, understand, and imitate human behavior in various contexts. The purpose of this research is to determine the effect of AI on students. The objects of this research were students at the Muhammadiyah University of Riau (UMRI) from various departments. The method used is a descriptive qualitative research method. With this method we can interview, observe, and distribute questionnaires to students to find out how influential AI is on UMRI students. The results of this research can be said that most UMRI students have used AI tools in their lecture activities. On the one hand, 60% of them said that AI had a positive impact on them because AI could help them find answers to assignments, help them search, provide references in writing articles, and help them complete other activities or tasks. However, the remaining 40% of students also said that AI also had a bad impact on them because AI made students lazy to think, lazy to develop their abilities, and knowledge.